dic-evaluative experiences in the university context: the evaluation from a learning community (2019)
Ludic Evaluation is an assessment practice that aims to assess students’ performance through playful experiences which offer timely and relevant information about their learning and reduce levels of anxiety that are usually found in traditional assessment experiences. The objective of the present study was to understand the classroom interactions that are generated when performing evaluation experiences mediated by games in the context of a university teaching learning community. It was a descriptive study in which experiences of self-assessment were carried out with 160 students at a private Colombian university. These experiences were carried out in 5 phases: theoretical foundation, diagnosis, design, application and reflection. Results show a change in the perception of students of the evaluative processes, in which positive emotions such as enthusiasm, joy and safety were highlighted. Based on these results, it was concluded that it is possible to assess learning in less stressful scenarios than those usually found in traditional normative and quantitative assessment.